2013
DOI: 10.1097/sap.0b013e31828637ec
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Pain Following Abdominal Free Flap Breast Reconstruction

Abstract: Factors contributing to chronic pain continue to be elusive and understudied. Our data demonstrate the importance of screening for chronic pain, as we determined that preoperative pain is linked to increased, moderately debilitating postoperative chronic pain. Persistent chronic pain, in turn, is associated with significant morbidity, disability, and dissatisfaction. Such patients with pain issues may benefit from additional preoperative counseling and early involvement of the pain service.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 39 publications
0
11
0
1
Order By: Relevance
“…Comparative studies on the risk of CPSP following TE/I and AFR reconstructive surgeries have produced mixed findings demonstrating greater postoperative pain with TE/I compared to breast reconstruction without implants, 14 equivocal evidence for increased pain with TE/I reconstruction, 15 more pain following AFR surgery compared to TE/I reconstruction, 12 or no differences in the severity of persistent postoperative pain between the two procedure types. 7,10,11 One explanation for this lack of agreement among previous studies may be that relative differences in postoperative pain among procedure types may evolve over time. This has been the observation in our own study population.…”
Section: Discussionmentioning
confidence: 95%
“…Comparative studies on the risk of CPSP following TE/I and AFR reconstructive surgeries have produced mixed findings demonstrating greater postoperative pain with TE/I compared to breast reconstruction without implants, 14 equivocal evidence for increased pain with TE/I reconstruction, 15 more pain following AFR surgery compared to TE/I reconstruction, 12 or no differences in the severity of persistent postoperative pain between the two procedure types. 7,10,11 One explanation for this lack of agreement among previous studies may be that relative differences in postoperative pain among procedure types may evolve over time. This has been the observation in our own study population.…”
Section: Discussionmentioning
confidence: 95%
“…The introduction of muscle-sparing free transverse rectus abdominis myocutaneous (TRAM) flap and deep inferior epigastric perforator (DIEP) reconstruction has significantly contributed to improved patient outcomes. However, opioid-related adverse drug events, such as nausea and constipation, continue to be a problem in the postoperative setting for patients with breast cancer (1, 2). Recently, there has been an increased focus on using enhanced recovery pathways (ERPs) in reconstructive breast surgery to further improve outcomes, such as early mobilization, optimization of pain control, and earlier hospital discharge (35).…”
Section: Introductionmentioning
confidence: 99%
“…Nelson et al . found that development of CPSP after mastectomy and reconstruction after 4 months was associated with the incidence of preoperative pain.…”
Section: Discussionmentioning
confidence: 81%
“…found that development of CPSP after mastectomy and reconstruction after 4 months was associated with the incidence of preoperative pain. Higher preoperative pain scores, lower mental health, and poor physical health scores at baseline were associated with the development of CPSP . Other variables such as laterality, timing of procedure, or type of flap used were not significantly associated with the development of CPSP.…”
Section: Discussionmentioning
confidence: 99%